The effectiveness of intervention to reduce blood-borne pathogen exposure incidents in healthcare workers in the largest clinical setting in Slovenia - Šestan, Nevenka (Zdravstveno varstvo, 2025)
Aim: Aimed at evaluating the effectiveness of intensified organised training programmes introduced in 2016 and 2017 for raising awareness of the problem of blood-borne incidents (BBIs), the objective was to analyse the incidence of reported BBIs (RBBI) over a 15-year period in different groups of healthcare workers (HCWs) employed at the University Medical Centre in Ljubljana (UMCL). Methods: All UMCL incidents that occurred and were reported from 1 January 2008 to 31 December 2022 were included in the study. The entire period was divided into two observation periods, 2008-2017 and 2017-2022. For testing a linear trend, whenever applicable a piecewise/segmented linear regression was applied, with the year 2017 as a break-point. Results: In the 2008–2017 period, the trend of annual incidence risk was mostly on the increase. The increase was statistically significant in medical doctors (MDs) and dental medicine doctors (DMDs) (p<0.001) as well as in other occupational groups (p=0.015). In the 2017-2022 period, the decrease was statistically significant in females (p=0.011), in MDs and DMDs (p=0.007), in nurses (p=0.021) and in HCWs in the Surgery Division (p=0.023). Conclusion: The results of the present study suggest that measures introduced in the UMCL were partially effective. The findings could serve as a basis for the development of improved programmes for better prevention, reporting and reducing the consequences of blood-borne pathogen exposure incidents among HCWs not only in Slovenia, but also worldwide.
Keywords: large clinical setting; nezgode pri delu; occupational incidents; ostri predmeti; sharps; velike zdravstvene ustanove